DENGUE HEMORRHAGIC FEVER (DHF) EDUCATIVE GAME TO IMPROVE KNOWLEDGE AND SKILL OF ELEMENTARY SCHOOL CHILDREN IN DHF PREVENTION - Susanto, Abiyyu Naufal; Maryana, Maryana; Khasanah, Titik Fajriyati Nur; Deastuti, Francilia; Chrisnajayantie, Raden Roro Brilianti; Nurlitasari, Anggita (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The Ministry of Health of the Republic of Indonesia released data on the number of dengue fever sufferers in Indonesia on January 29, 2019 there are 13,683 cases and increased to 16,692 cases on February 3, 2019. The Director General of Disease Prevention and Control said that 90% of cases of dengue fever were children under age of 15 years.The Ministry of Health noted the number of cases of dengue hemorrhagic fever (DHF) in January 2019 increased to 121.8% compared to January last year. This study aims to examine the effect of educational games on increasing the knowledge and skills of elementary school age children about the prevention of dengue fever. Methods: To test the hypothesis, this study uses experimental research methodology to determine the results of treatment of a particular group to produce an innovation and recommendations for prevention of dengue fever in children. Results: This educational game can increase children's interest in learning to prevent dengue fever and improve their ability to prevent dengue fever. Educational games methods for elementary school age children can influence children's understanding and skills in preventing dengue fever at the age of elementary school children. This study was able to describe the effect of educational game with clean and healthy behaviour that more effective to prevent the incidence of dengue fever in elementary school- aged children. Conclusion: This educational game needs to be continuously applied and developed to reduce the incidence of dengue fever in children under 15 years of age. In the future, researchers should have to developed more modern design it can be like a virtual game that more atractive for the children. So, the goals of this research can be achieved.